The influence of cooperative learning on students' communication skills / Noorliza Mohd Noor - Mohd Noor, Noorliza (2014)
This paper reports on a study designed to investigate and identify (1) In what ways do Cooperative Learning influence communication skills?, (2) In what ways do Cooperative Learning create positive interdependence?, and (3) In what ways do Cooperative Learning influence students’ accountability? Participants were 150 English Second Language (ESL) learners of Matrikulasi Melaka. Data include respondents’ response to a questionnaire and interview questions. Analyses and comparison of the learners’ responses show that Cooperative Learning provides them more opportunity to communicate in English thus are advantage compare to traditional teaching method.The three activities are prepared for the students such as Story Writing, Story Telling and Product Promotion. It is carried out based on the Cooperative Learning method in order for the students to answer the questions and give their responses and opinion regarding the Cooperative Learning method. Furthermore, students also need to sit for face and face interview session related to Cooperative Learning Method. Based on the findings, it shows that Cooperative Learning Method is able to influence students communication skills, as well students individual accountability and positive interdependence. However, there are some drawbacks and limitations addressed in this study. The results of this study are interpreted with an understanding of its limitations and directions for further research are also discussed. This study has provide evidence that Cooperative Learning is an effective teaching method in teaching English as it able to improved learners’ communication skills, encourage Positive Interdependence among peers and enhancing learners’ accountability although the effects vary among learners. Cooperative Learning Method provides new experience on learners which are not available in the usual traditional teaching method.